Population-based prevalence of oral conditions as a basis for planning community-based interventions: an epidemiological study from rural Burkina Faso - Clauss, Alexandra; Sié, Ali; Zabré, Pascal; Schmoll, Jörg; Sauerborn, Rainer; Listl, Stefan (Frontiers in Public Health, 2021)
Objectives: The purpose of the present study was to: (i) provide timely data on dental caries and periodontal conditions in rural Burkina Faso; (ii) identify the oral health practices carried out in this population, and (iii) to prioritize evidence-based interventions at the community level. Methods: Leaning on WHO recommendations for oral health epidemiological studies, clinical examinations and questionnaire-based surveys were conducted in two different age groups (adolescents: 15-19 years old; adults: 35-44 years old) in the health district of Nouna, Burkina Faso. Caries and tooth status were assessed according to the DMFT Index. The periodontal status was assessed by a modified Community Periodontal Index on all teeth present and measuring the level of attachment-loss of 6 index teeth. Questionnaire items specifically included utilization of oral health care and oral health behaviors. Results: The prevalence of untreated caries was 38% in adolescents and 73% in adults. In terms of periodontal health, 21% of adolescents and 61% of adults had an attachment loss ≥ 4mm. 97% of adolescents had not attended a dentist in the previous year and 78% of adults had never seen a dentist in their life. About one third of adolescents and adults cleaned their teeth less often than once per day with equal proportions of toothbrushes and traditional chewing sticks made of tree branches. Fluoride toothpaste was used by less than ten percent of study participants. Almost half of the examined people reported to drink a sugar-sweetened beverage at least once a day. Conclusions: Dental caries and periodontitis are highly prevalent in rural Burkina Faso. These findings highlight the key relevance of epidemiological data for identifying people’s oral health needs as basis for developing, testing, and implementing oral health interventions and programs. Special emphasis should be put on the design and evaluation of community-based interventions.
Gesehen am 13.07.2021